Association of childhood-to-adolescence body mass index trajectories with elevated blood pressure and elevated carotid intima-media thickness - Xie, Jintang; Liu, Ziqi; Zhao, Min; Ma, Chuanwei; Xi, Bo (Frontiers in Nutrition, 2025)
BackgroundLimited evidence exists on how early-life weight changes relate to cardiovascular damage in adolescents. We aimed to investigate the association between body mass index (BMI) trajectories from childhood to adolescence and elevated blood pressure (BP) and elevated carotid intima-media thickness (cIMT) in adolescents.MethodsThis study included a total of 1,405 participants from the Huantai Children’s Cardiovascular Health Cohort who had at least two BMI measurements between 2017 and 2023. Group-based trajectory modeling was used to identify distinct BMI trajectories. Logistic regression models were used to analyze the association between these BMI trajectories and the development of elevated BP and elevated cIMT.ResultsThe BMI trajectory patterns of participants from childhood to adolescence were categorized into three groups: low-and-increasing (n = 473, 33.67%), medium-and-increasing (n = 533, 37.94%) and high-and-increasing (n = 399, 28.40%). Compared to the low-and-increasing group (systolic BP [SBP]: 110.16 mmHg, diastolic BP [DBP]: 60.59 mmHg, cIMT: 0.549 mm), the medium-and-increasing group had higher SBP (114.14 mmHg) and cIMT (0.567 mm), along with an increased risk of elevated BP (odds ratio [OR] 2.50, 95% confidence interval [CI] 1.43–4.39) and elevated cIMT (OR 3.17, 95% CI 1.50–6.74) (all p < 0.05). Similarly, the high-and-increasing group exhibited higher SBP (122.85 mmHg), DBP (62.83 mmHg), and cIMT (0.595 mm), as well as an increased risk of elevated BP (OR 10.73, 95% CI 6.23–18.48) and cIMT (OR 18.91, 95% CI 9.19–38.89) (all p < 0.05).ConclusionConsistently elevated BMI from childhood to adolescence is closely associated with elevated BP and elevated cIMT during adolescence. Obesity prevention and screening in youth should be prioritized to reduce future cardiovascular disease risk.